Estimation of Chromatographic Columns Performances using Computer Tomography and CFD Simulations - Schmidt, Irma; Lottes, Florian; Minceva, Mirjana; Arlt, Wolfgang; Stenby, Erling H. (Chemie Ingenieur Technik, 2011)
The flow inside a chromatographic column depends decisively on the packed bed inside. Non-destructive X-ray computed tomography (CT) was applied as a novel measurement technique to visualize the distribution of velocity and axial dispersion coefficients in preparative scale columns. The results show, that spherical particles seem to be more efficient than irregular ones in terms of HETP, which has to be partly a result of the more homogeneous flow profile they induce. The prediction of column performance in dependence of the structure of the packed bed was simulated by CFD (Computational Fluid Dynamics), using a model which besides the hydrodynamics parameters attained by CT also includes adsorption isotherms and mass transfer parameters. The results of the CFD simulation shall help to establish rules for selecting the right adsorption material for a given separation task in advance.
Keywords: CFD; Chromatography; Column; Computer tomography